2011
DOI: 10.1016/j.jelechem.2011.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous stripping detection of Zn(II), Cd(II) and Pb(II) using a bimetallic Hg–Bi/single-walled carbon nanotubes composite electrode

Abstract: A new, sensitive platform for the simultaneous electrochemical assay of Zn(II), Cd(II) and Pb(II) in aqueous solution has been developed. The platform is based on a new bimetallic Hg-Bi/single-walled carbon nanotubes (SWNTs) composite modified glassy carbon electrode (GCE), demonstrating remarkably improved performance for the anodic stripping assay of Zn(II), Cd(II) and Pb(II). The synergistic effect of Hg and Bi as well as the enlarged, activated surface and good electrical conductivity of SWNTs on GCE contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
61
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(68 citation statements)
references
References 32 publications
0
61
0
4
Order By: Relevance
“…Bismuth (Bi) is a semimetal with a lot of unique electrical, physical and chemical properties such as large Fermi wavelengths, strong diamagnetism, high magnetoresistance, excellent catalytic and electrochemical performance [1][2][3]. Compared with other heavy metals, Bi has relatively low toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Bismuth (Bi) is a semimetal with a lot of unique electrical, physical and chemical properties such as large Fermi wavelengths, strong diamagnetism, high magnetoresistance, excellent catalytic and electrochemical performance [1][2][3]. Compared with other heavy metals, Bi has relatively low toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…In the study, LOD of Cd 2+ and Pb 2+ were determined as 2.8 and 0.55 μg L −1 , respectively. Ouyang et al (2011) analyzed Zn 2+ , Cd 2+ , and Pb 2+ on the Hg-Bi included carbon nanotube modified GC electrode by SWV. They reported that the LODs for Cd 2+ and Pb 2+ were lower than 2 ppm and 0.12 ppb, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…According to the assumptions above, a crucial point to the success of a voltammetric technique is the choice of a suitable working electrode [6,16]. Ideally, a suitable working electrode must provide a good analytical performance (high sensitivity, robustness, stability, low detection limits and application in a wider range of concentrations); additionally, the electrode should be nontoxic, operate using cost-efficient technology and be free of organic and or intermetallic interferences.…”
Section: Introductionmentioning
confidence: 99%